1988
DOI: 10.1121/1.397184
|View full text |Cite
|
Sign up to set email alerts
|

Four channels mediate the mechanical aspects of touch

Abstract: Although previous physiological and anatomical experiments have identified four afferent fiber types (PC, RA, SA II, and SA I) in glabrous (nonhairy) skin of the human somatosensory periphery, only three have been shown to mediate tactile (mechanoreceptive) sensation. Psychophysical evidence that four channels (P, NP I, NP II, and NP III) do, indeed, participate in the perceptual process is presented. In a series of experiments involving selective masking of the various channels, modification of the skin-surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

41
619
3
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 791 publications
(669 citation statements)
references
References 42 publications
41
619
3
6
Order By: Relevance
“…Psychophysical studies have shown that with the contact conditions used in the current study the thresholds at these low frequencies are not mediated by the Pacinian channel but by another channel, probably NPI associated with Meissner corpuscles (Bolanowski et al, 1988). The four channel psychophysical model suggests that around 25 dB SL above the absolute thresholds for these frequencies, one or more other channel, including the P-channel, become activated and involved in the mediation of sensations (Bolanowski et al, 1988). The results suggest finger blood flow reduced when the vibration magnitude was sufficient to activate the Pacinian receptors, which occurs at threshold levels at high frequencies but at magnitudes much greater than the threshold at low frequencies.…”
Section: Finger Blood Flow After Vibration Exposurementioning
confidence: 63%
See 4 more Smart Citations
“…Psychophysical studies have shown that with the contact conditions used in the current study the thresholds at these low frequencies are not mediated by the Pacinian channel but by another channel, probably NPI associated with Meissner corpuscles (Bolanowski et al, 1988). The four channel psychophysical model suggests that around 25 dB SL above the absolute thresholds for these frequencies, one or more other channel, including the P-channel, become activated and involved in the mediation of sensations (Bolanowski et al, 1988). The results suggest finger blood flow reduced when the vibration magnitude was sufficient to activate the Pacinian receptors, which occurs at threshold levels at high frequencies but at magnitudes much greater than the threshold at low frequencies.…”
Section: Finger Blood Flow After Vibration Exposurementioning
confidence: 63%
“…Although thresholds at low frequencies are determined by the responses of a non-Pacinian channel, other mechanoreceptors become activated at greater magnitudes of vibration (Bolanowski et al, 1988;Verrillo et al, 2002). At vibration magnitudes 25, 30, and 40 dB SL above the threshold, the Pacinian channel is expected to have been activated.…”
Section: Finger Blood Flow After Vibration Exposurementioning
confidence: 99%
See 3 more Smart Citations